(untitled) (Journal of Environmental Science and Natural Resources, 2012)
Arsenic (As) consumption through foods by adults and children in the As contaminated Marua village of Chowgacha upazila under Jessore district was studied. The Asian Arsenic Network (AAN) and the Japanese International Cooperation Agency (JICA) have provided some interventions such as installation of deep tube-wells and As-Fe removal plants and awareness program to reduce drinking water As exposure of people living in the village. But scope exists for food crops grown in this area to accumulate As from As contaminated irrigation water. With these points in view, a household food survey was made to investigate As intake by the people living in Marua village. For it, cooked meals and uncooked foods were collected from households and local market. The study revealed that an adult consumed 220 ?g As per day from food source and rice alone contributed 86% of it. Considering 80% inorganic As in rice, 220 ?g total As is equivalent to 176 ?g As which exceeds the WHOs provisional maximum tolerable daily intake of As which is 2 ?g/kg body weight i.e. 120 ?g As for a 60 kg person. This result suggests that next to drinking water, food (mainly rice) is the principal source of As entry into human body in Bangladesh. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11593 J. Environ. Sci. & Natural Resources, 5(1): 283-288, 2012